On the mode structure of imperfect fluids - Zimdahl, Winfried (Cadernos de Astronomia, 2022)
This paper tries to present a simple picture of several aspects of the mode structure in relativistic non-equilibrium thermodynamics. Its pedagogical focus is on the relation between long-wavelength perturbation modes of the causal Müller-Israel-Stewart (MIS) theory and those of the traditional Eckart theory. Principally, this issue was clarified in a series of papers by Hiscock and Lindblom. Here, I put together some essential features of this topic which do not require the entire formalism of the complete theory.